Bahan Ajar Berbasis Mathematical Comic: Dampak Terhadap Peningkatan Pemahaman Matematis Peserta Didik - Komarudin Komarudin; Andi Thahir; sholekan sholekan (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2019)
The mathematical understanding of learners is one of the successful mathematical subjects. To make a success from a math lesson that one aspect of it is mathematical understanding. To increase the mathematical understanding of learners, it is necessary to develop a decent, attractive and effective mathematical teaching material. So the purpose of this research is to develop MATCOM-based materials to improve the understanding of students math Class VII Junior high School in Bandar Lampung. This research includes research and Development (R&D) studies and uses ADDIE (Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation) procedures in its development. Data retrieval techniques are carried out with polls and tests. As for the research instrument used is a feasibility questionnaire, response questionnaire and a test of understanding of the concept. The results showed that MATCOM-based teaching materials gained an average score of 3.56 eligibility for material experts and 3.56 for media experts with decent criteria. And gained an average score of 3.65 with very interesting criteria. And based on the effective test results of MATCOM-based teaching materials have a score of 0.54 with moderate Kateogri. So it can be concluded that MATCOM based teaching materials are very decent and attractive and able to enhance the mathematical understanding of class VII Junior high School in Bandar Lampung.